Bi-metal atom catalyst with Fe-Cu structure as well as preparation method and application of bi-metal atom catalyst

By using the Fe-Cu structure bimetallic atomic catalyst in the advanced persulfate oxidation technology, the problems of high energy consumption and serious secondary pollutants are solved, and the low-cost and efficient pollutant removal effect is achieved.

CN119215949APending Publication Date: 2024-12-31JIANGSU SUPERVISION & INSPECTION INST FOR PROD QUALITY

Patent Information

Application Number
CN202411271441.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, the advanced persulfate oxidation technology has problems of high energy consumption and serious secondary pollutants. The traditional thermal activation, alkali activation and metal ion activation efficiency are low, and a non-precious metal catalyst is needed to solve these problems.

Method used

By calcining urea, 1,10-phenanthoroline, soluble iron salt and copper salt under a nitrogen atmosphere, a bimetallic atomic catalyst with a Fe-Cu structure is formed and used during the activation of persulfate, using 1, The complexes and graphene structure formed by 10-phenanthroline and urea improve the activation efficiency of the catalyst.

Benefits of technology

It realizes low-cost and efficient pollutant removal, improves the success rate and activation efficiency of catalyst synthesis, reduces the generation of secondary pollutants, and is economical and easy to obtain raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215949A_ABST
    Figure CN119215949A_ABST
Patent Text Reader

Abstract

The invention discloses a bimetallic atom catalyst with a Fe-Cu structure as well as a preparation method and application of the bimetallic atom catalyst, and belongs to the field of environmental remediation materials. The method comprises the following steps: (1) mixing and pretreating urea, 1, 10-phenanthroline, soluble iron salt and copper salt, and calcining in a nitrogen atmosphere; and (2) washing and drying the calcined product obtained in the step (1) to obtain the bimetallic atom catalyst with the Fe-Cu structure. The preparation method is simple in steps and easy to amplify, and the prepared monatomic catalyst has good performance of activating peroxymonosulfate (PMS).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental restoration materials, and in particular to a bimetallic atom catalyst having an Fe-Cu structure prepared by a simple thermal reaction, a preparation method thereof, and an application thereof in a peroxymonosulfate activation process. Background Art

[0002] Persulfate-based advanced oxidation technology is one of the key research technologies for soil and groundwater pollution remediation. It mainly activates persulfate to produce active substances, thereby degrading organic pollutants and achieving the purpose of repairing organic pollution in soil and groundwater. However, there are still some challenges for persulfate advanced oxidation technology. Traditional thermal activation, alkali activation, metal ion and oxide activation have problems such as high energy consumption and serious secondary pollutants. Therefore, developing a non-precious metal catalyst that can effectively activate persulfate is an effective solution to this problem. On this basis, single-atom catalysts were proposed and received widespread attention from experts at home and abroad.

[0003] Single-atom catalysts refer to structures in which the active metal is dispersed on a carrier in the form of a single atom, and each metal atom has a certain distance between them. Compared with conventional catalysts, the utilization rate of metal atoms in single-atom catalysts is maximized, and they exhibit excellent performance in a variety of catalytic reactions. However, single-atom catalysts have shortcomings in structure and selective activation because they only have one metal atom. Bimetallic atom catalysts based on different atomic pairs can not only regulate the structure of the catalyst by the type of transition metal atoms, but also achieve selective activation, effectively expanding the application scope of persulfate advanced oxidation technology.

[0004] After searching, two patent documents related to the present case were found. Among them, the Chinese patent with publication number CN115007187A provides a nickel-iron bimetallic single-atom catalyst for direct activation of nitrogen-doped graphene for treating phenol-containing wastewater with persulfate, wherein the precursor is obtained by mixing large-defect graphene oxide, nickel salt, iron salt and dicyandiamide, freeze-drying, and then high-temperature treatment under a nitrogen atmosphere to obtain an iron-nickel bimetallic single-atom catalyst. This scheme is significantly different from the present invention. The preparation method provided by the present invention is simple and easy, the raw materials are economical and easy to obtain, and the prepared bimetallic atom catalyst has a special Fe-Cu atomic pair structure. The Chinese patent with publication number CN 113181918A provides a non-metallic mineral-induced double single-atom catalyst and its preparation and application, which is mainly through the natural non-metallic minerals uniformly dispersed in water, and the transition metal salt and carbon source are added, reacted under the condition of pH value of 7-10, to obtain a solid mixture, and then roasted and acid-washed to obtain the MSi double single-atom catalyst. Different from the preparation method provided by the present invention, the present invention is mainly synthesized directly through a one-pot method, and does not need to add non-metallic minerals as inducers. Summary of the invention

[0005] The purpose of the present invention is to provide a bimetallic atom catalyst having a Fe-Cu atomic pair structure, a preparation method thereof, and an application thereof in activating peroxymonosulfate to remove pollutants in water. The bimetallic atom catalyst synthesis method of the present invention has economical and readily available raw materials, a simple and easy preparation method, and can solve the technical problems existing in the prior art.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] In a first aspect, the present invention claims a method for preparing a bimetallic atom catalyst having a Fe-Cu structure, the method comprising the following steps:

[0008] (1) urea, 1,10-phenanthroline, a soluble iron salt and a copper salt are mixed and pretreated, and then calcined under a nitrogen atmosphere;

[0009] (2) The calcined product obtained in (1) is rinsed and dried to obtain a bimetallic atom catalyst having an Fe-Cu structure.

[0010] Furthermore, in step (1), the molar ratio of the soluble iron salt to the copper salt is 4:1 to 1:4; the soluble iron salt and the copper salt are soluble metal salts; the molar ratio of the urea, 1,10-phenanthroline and the soluble metal salt is 100:10 to 20:1 to 5; preferably, the molar ratio of urea, 1,10-phenanthroline and the soluble metal salt is 100:10:1.

[0011] Furthermore, the mixed pretreatment process in step (1) is as follows: firstly dissolving 1,10-phenanthroline, soluble iron salt and copper salt in ethanol, and stirring at 60-80°C for 0.5-1 hour, then adding urea and ultrasonically treating for 30-60 minutes; and drying at 70-80°C until all ethanol is volatilized.

[0012] Furthermore, before calcination in step (1), the pre-treated urea, 1,10-phenanthroline, soluble iron salt and copper salt are semi-sealed. In a specific embodiment of the present invention, a container such as a crucible containing urea, 1,10-phenanthroline, soluble iron salt and copper salt is covered and wrapped with aluminum foil for semi-sealing.

[0013] Furthermore, the soluble iron salt and copper salt described in step (1) are iron nitrate and copper nitrate.

[0014] Furthermore, the programmed annealing in step (1) is the calcination procedure as follows: a heating rate of 5°C / min, annealing at 500-520°C for 2 hours, then heating to 700-800°C for annealing for 2 hours, and finally cooling naturally.

[0015] Furthermore, the rinsing in step (2) is performed by alternately rinsing with 0.05-0.10 mol / L sulfuric acid solution, 50%-70% ethanol solution and ultrapure water for 3-5 times.

[0016] In a second aspect, the present invention claims protection for a bimetallic atom catalyst having a Fe-Cu structure prepared by the above method.

[0017] In a third aspect, the present invention seeks to protect the use of the above-mentioned bimetallic atom catalyst having a Fe-Cu structure in activating peroxymonosulfate to remove pollutants in water.

[0018] In the further described application: during the process of activating peroxymonosulfate, the pH value of the reaction solution is 3-9.

[0019] Mechanism of the present invention:

[0020] 1,10-phenanthroline can form a complex with iron or copper. Since the complex formed is a chelate, it is relatively stable. Urea is added to the reaction system as a nitrogen source. Since urea forms a graphite phase carbon nitride (g-C3N4) with a tri-s-triazine structure at 500℃~520℃, it can not only fix free iron and copper ions, but also connect the complex formed by 1,10-phenanthroline and iron or copper. During the reaction, the defective ring structure formed by two 1,10-phenanthroline molecules can accommodate iron and copper atoms to form a Fe-Cu structure. As the temperature continues to rise to 700~800℃, a small amount of unstable structures will be destroyed to form a graphene sheet structure. The Fe-Cu structure is coordinated by nitrogen atoms and is relatively stable. It can be retained during the acid washing and water washing process to form a bimetallic atomic catalyst with a Fe-Cu structure.

[0021] Beneficial effects of the present invention:

[0022] (1) The mixing process of 1,10-phenanthroline, iron nitrate and copper nitrate will form a metal complex, which is conducive to the dispersion and coordination of metal ions. It avoids the agglomeration of metal atoms on the support surface and greatly improves the success rate of the synthesis of bimetallic atom catalysts;

[0023] (2) In the synthesis process of this material, 1,10-phenanthroline, iron nitrate and copper nitrate are firstly coordinated, and then urea is added as a nitrogen source to further improve the success rate of the synthesis;

[0024] (3) The synthesis temperature is controlled by programmed temperature rise, 500-520 °C is for the formation of g-C3N4, which is conducive to the formation of Fe-Cu atomic pairs, and 700-800 °C is for further forming the graphene structure and improving the activation efficiency of the material for peroxymonosulfate.

[0025] (4) The synthetic raw materials used are cheap and widely available. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Transmission electron microscopy (TEM) of the Fe-Cu bimetallic atom catalyst prepared in Example 1 of the present invention;

[0027] Figure 2 This is a phase-corrected high-angle annular dark field scanning transmission electron microscopy (HADDF-STEM) photograph of the Fe-Cu bimetallic atom catalyst prepared in Example 1 of the present invention;

[0028] Figure 3 X-ray diffraction (XRD) pattern of the Fe-Cu bimetallic atom catalyst prepared in Example 1 of the present invention.

[0029] Figure 4Examples 1-3 of the present invention are comparison diagrams of activation of peroxymonosulfate by corresponding bimetallic atom catalysts prepared by varying the ratio of urea to cobalt nitrate hexahydrate. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Unless otherwise specifically stated, the relative arrangement of the parts and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present invention. The techniques, methods and equipment known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the techniques, methods and equipment should be considered as part of the authorization specification.

[0032] The present invention is described in detail below with reference to the accompanying drawings to facilitate those skilled in the art to understand the present invention.

[0033] The drugs used in the present invention are all purchased from the market without further purification.

[0034] Example 1

[0035] 1.982g of 1,10-phenanthroline monohydrate (molecular weight: 198.22, 10mmol), 0.202g of Fe(NO3)3·9H2O (molecular weight: 404.00, 0.5mmol) and 0.121g of Cu(NO3)2·3H2O (molecular weight: 241.60, 0.5mmol) were placed in a 50ml crucible, followed by 40ml of ethanol, and stirred at 60°C for 1 hour on a constant temperature magnetic stirrer. 6g of urea (molecular weight: 60.06, 100mmol) was then added, and the crucible was ultrasonically treated for 1 hour, and then the crucible containing the mixed solution was placed in an oven at 80°C and taken out after the solution was completely evaporated. The crucible was covered with a lid and wrapped with aluminum foil for semi-sealing. The crucible was placed in a tube furnace, heated to 520°C at 5°C / min for 2 hours under N2 atmosphere, then heated to 800°C at 5°C / min for 2 hours, cooled to room temperature, and then rinsed the product three times alternately with 0.10 mol / L sulfuric acid solution, 70% (v / v) ethanol solution and ultrapure water, and finally washed with ultrapure water until neutral. The washed product was placed in an oven at 80°C for drying to obtain the target catalyst FeCuCN.

[0036] FeCuCN and potassium permonosulfate (PMS) were mixed (the pH value of the reaction solution was 7) to remove bisphenol A in the solution, and the concentration of PMS in the solution was measured, the same below.

[0037] Comparative Example 1

[0038] 1.982g of 1,10-phenanthroline monohydrate and 0.404g of Fe(NO3)3·9H2O were placed in a 50ml crucible, followed by the addition of 40ml of ethanol, and stirred at 60°C on a constant temperature magnetic stirrer for 1 hour. 6g of urea was then added, and the crucible was ultrasonically treated for 1 hour, and the crucible containing the mixed solution was placed in an oven at 80°C and taken out after the solution was completely evaporated. The crucible was covered with a lid and wrapped with aluminum foil for semi-sealing. The crucible was placed in a tube furnace, heated to 520°C at 5°C / min for 2 hours under N2 atmosphere, and then heated to 800°C at 5°C / min for 2 hours. After cooling to room temperature, the product was alternately rinsed 3 times with 0.10mol / L sulfuric acid solution, 70% ethanol solution and ultrapure water, and finally washed with ultrapure water until neutral. The washed product was placed in an oven at 80°C for drying to obtain the target catalyst FeCN.

[0039] Comparative Example 2

[0040] 1.982g of 1,10-phenanthroline monohydrate and 0.242g of Cu(NO3)2·3H2O were placed in a 50ml crucible, followed by the addition of 40ml of ethanol, and stirred at 60°C for 1 hour on a constant temperature magnetic stirrer. 6g of urea was then added, and the crucible was ultrasonically treated for 1 hour, and the crucible containing the mixed solution was placed in an oven at 80°C, and the solution was taken out after being completely evaporated. The crucible was covered with a lid and wrapped with aluminum foil for semi-sealing. The crucible was placed in a tube furnace, heated to 520°C at 5°C / min for 2 hours under N2 atmosphere, and then heated to 800°C at 5°C / min for 2 hours. After cooling to room temperature, the product was alternately rinsed 3 times with 0.10mol / L sulfuric acid solution, 70% ethanol solution and ultrapure water, and finally washed with ultrapure water until neutral. The washed product was placed in an oven at 80°C for drying to obtain the target catalyst CuCN.

[0041] Example 2

[0042] 1.982g of 1,10-phenanthroline monohydrate (molecular weight: 198.22, 10mmol), 0.3232g of Fe(NO3)3·9H2O (molecular weight: 404.00, 0.8mmol) and 0.0484g of Cu(NO3)2·3H2O (molecular weight: 241.60, 0.2mmol) were placed in a 50ml crucible, followed by 40ml of ethanol, and stirred at 60°C for 1 hour on a constant temperature magnetic stirrer. 6g of urea (molecular weight: 60.06, 100mmol) was then added, and the crucible was ultrasonically treated for 1 hour, and then the crucible containing the mixed solution was placed in an oven at 80°C and taken out after the solution was completely evaporated. The crucible was covered with a lid and wrapped with aluminum foil for semi-sealing. The crucible was placed in a tube furnace, heated to 520°C at 5°C / min for 2 hours under N2 atmosphere, then heated to 800°C at 5°C / min for 2 hours, cooled to room temperature, and then rinsed the product three times alternately with 0.10 mol / L sulfuric acid solution, 70% ethanol solution and ultrapure water, and finally washed with ultrapure water until neutral. The washed product was dried in an oven at 80°C to obtain the target catalyst Fe4CuCN.

[0043] Example 3

[0044] 1.982g of 1,10-phenanthroline monohydrate (molecular weight: 198.22, 10mmol), 0.0808g of Fe(NO3)3·9H2O (molecular weight: 404.00, 0.2mmol) and 0.1936g of Cu(NO3)2·3H2O (molecular weight: 241.60, 0.8mmol) were placed in a 50ml crucible, followed by 40ml of ethanol, and stirred at 60°C for 1 hour on a constant temperature magnetic stirrer. 6g of urea (molecular weight: 60.06, 100mmol) was then added, and the crucible was ultrasonically treated for 1 hour, and then the crucible containing the mixed solution was placed in an oven at 80°C and taken out after the solution was completely evaporated. The crucible was covered with a lid and wrapped with aluminum foil for semi-sealing. The crucible was placed in a tube furnace, heated to 520°C at 5°C / min for 2 hours under N2 atmosphere, then heated to 800°C at 5°C / min for 2 hours, cooled to room temperature, and then rinsed the product three times alternately with 0.10 mol / L sulfuric acid solution, 70% ethanol solution and ultrapure water, and finally washed with ultrapure water until neutral. The washed product was dried in an oven at 80°C to obtain the target catalyst FeCu4CN.

[0045] Figure 1 This is a TEM image of the single-atom catalyst SA-CoCN prepared in Example 1. It can be seen that there are no iron and copper nanoparticles in the catalyst.

[0046] Figure 2This is a HADDF-TEM image of the Fe-Cu bimetallic atom catalyst prepared in Example 1, where the bright spots in the image are iron or copper atoms due to the difference in atomic contrast.

[0047] Figure 3 The XRD patterns of Example 1, Comparative Example 1 and Comparative Example 2 show that the diffraction peak positions of the two samples are almost the same, both of which are XRD diffraction peaks of graphene. It is preliminarily determined that there are no metal or metal oxide particles in the FeCuCN catalyst. Figure 1 and Figure 2 The results are consistent.

[0048] Figure 4 The performance comparison diagram of the activated permonosulfate of Examples 1-3 and Comparative Examples 1-2 is as follows: 10 mg of the catalyst is added to 100 ml of a reaction solution containing 0.5 mM potassium permonosulfate and 10 mg / L bisphenol A, the degradation reaction is started, 1 ml of the reaction solution is taken within a specified time, and the permonosulfate content in the sample is determined.

[0049] The specific implementation cases in the above description demonstrate the feasibility of the present invention. The synthesis method of FeCuCN is simple, and it has higher catalytic performance than FeCN and CuCN, and has certain social and economic benefits.

Claims

1. A method for preparing a bimetallic atom catalyst having a Fe-Cu structure, characterized in that: The method comprises the following steps: (1) urea, 1,10-phenanthroline, a soluble iron salt and a copper salt are mixed and pretreated, and then calcined under a nitrogen atmosphere; (2) The calcined product obtained in (1) is rinsed and dried to obtain a bimetallic atom catalyst having an Fe-Cu structure.

2. The method according to claim 1, characterized in that The molar ratio of the soluble iron salt to the copper salt in step (1) is 4:1 to 1:4; the soluble iron salt and the copper salt are soluble metal salts; the molar ratio of the urea, 1,10-phenanthroline and the soluble metal salt is 100:10 to 20:1 to 5.

3. The method according to claim 1, characterized in that The mixed pretreatment process in step (1) is as follows: firstly dissolving 1,10-phenanthroline, soluble iron salt and copper salt in ethanol, and stirring at 60-80° C. for 0.5-1 hour, then adding urea and ultrasonically treating for 30-60 minutes; and drying at 70-80° C. until all ethanol is volatilized.

4. The method according to claim 3, characterized in that Before calcination in step (1), the mixed pretreated urea, 1,10-phenanthroline, soluble iron salt and copper salt are semi-sealed.

5. The method according to any one of claims 1 to 4, characterized in that: The soluble iron salt and copper salt described in step (1) are iron nitrate and copper nitrate.

6. The method according to claim 1, characterized in that The calcination procedure in step (1) is as follows: heating rate is 5°C / min, annealing at 500-520°C for 2 hours, then heating to 700-800°C for annealing for 2 hours, and finally cooling naturally.

7. The method according to claim 1, characterized in that The flushing described in step (2) is to use 0.05-0.10 mol / L sulfuric acid solution, 50%-70% ethanol solution and ultrapure water to flush alternately 3-5 times.

8. A bimetallic atom catalyst having a Fe-Cu structure prepared by the method described in any one of claims 1 to 7.

9. Use of the bimetallic atom catalyst having an Fe-Cu structure as claimed in claim 8 in activating peroxymonosulfate to remove pollutants in water.

10. The use according to claim 9, characterized in that: During the activation of peroxymonosulfate, the pH value of the reaction solution is 3-9.

Citation Information

Patent Citations

  • Nonmetallic mineral induced double-monatomic catalyst and preparation and application thereof

    CN113181918A

  • Nitrogen-doped graphene nickel-iron bimetallic monatomic catalyst for directly activating persulfate to treat phenolic wastewater

    CN115007187A

Cited By

  • Preparation method and application of catalytic material for efficiently activating peroxymonosulfate

    CN122377505A